2002
DOI: 10.1093/emboj/cdf411
|View full text |Cite
|
Sign up to set email alerts
|

CD44 directs membrane-type 1 matrix metalloproteinase to lamellipodia by associating with its hemopexin-like domain

Abstract: Membrane-type 1 matrix metalloproteinase (MT1-MMP) localizes at the front of migrating cells and degrades the extracellular matrix barrier during cancer invasion. However, it is poorly understood how the polarized distribution of MT1-MMP at the migration front is regulated. Here, we demonstrate that MT1-MMP forms a complex with CD44H via the hemopexin-like (PEX) domain. A mutant MT1-MMP lacking the PEX domain failed to bind CD44H and did not localize at the lamellipodia. The cytoplasmic tail of CD44H, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
297
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(321 citation statements)
references
References 51 publications
15
297
2
2
Order By: Relevance
“…As previously reported, MMP14 has been found to be mainly transported to the cell front of migrating cells [29]. Immunofluorescence studies shown in Supplementary information, Figure S1A revealed that MMP14 transport was affected by BFA: cells that were exposed to 7 µM BFA clearly showed an accumulation of MMP14 in close proximity to the nucleus (d), while in untreated control cells, MMP14 staining was mainly visible at the front membrane of the cell (a), as indicated by white arrows.…”
Section: Intracellular Transport Of Mia Protein Follows the Conventiosupporting
confidence: 78%
“…As previously reported, MMP14 has been found to be mainly transported to the cell front of migrating cells [29]. Immunofluorescence studies shown in Supplementary information, Figure S1A revealed that MMP14 transport was affected by BFA: cells that were exposed to 7 µM BFA clearly showed an accumulation of MMP14 in close proximity to the nucleus (d), while in untreated control cells, MMP14 staining was mainly visible at the front membrane of the cell (a), as indicated by white arrows.…”
Section: Intracellular Transport Of Mia Protein Follows the Conventiosupporting
confidence: 78%
“…10 -13 The CD44 -HA complex initiates a series of intracellular signaling events that lead to migration, adhesion, invasion, proliferation, and differentiation of a variety of cells. The transduction of HA/CD44 signaling can occur through various mechanisms including the following: i) HA binding to CD44 can initiate the extracellular clustering of CD44, resulting in the activation of downstream kinases, 14 ii) CD44 can serve as a co-receptor physically associated with other cell signaling receptors, [15][16][17][18] iii) CD44 can serve as a docking protein for pericellular or cytoplasmic proteins, 19,20 and iv) the transmembrane domain of CD44 can be cleaved, allowing the translocation of the cytoplasmic domain to the nucleus, where it functions as a transcription factor regulating the expression of target genes such as CD44 itself. 21,22 CD44 and its variants can induce chemoresistance and invasion of human BC cell lines via different mechanisms.…”
mentioning
confidence: 99%
“…79,80 In vitro and in vivo data similarly suggest that overexpression of MT1-MMP promotes HNSCC tumor cell invasion. 25,81 MT1-MMP plays a critical role in tumor cell invasion and angiogenesis through several known mechanisms: (1) activation of MMP-2, 77,82 (2) cleavage of the cell adhesion molecule CD44 from the cell surface, 83,84 (3) degradation of type I collagen and fibrin substrates, 29,85,86 and (4) enabling cell survival in three-dimensional matrices. 87 As a membrane-anchored collagenase, MT1-MMP remains localized to the cell surface, unlike secreted MMPs.…”
Section: Mt1-mmp As a Target For Selective Inhibition In Head And Necmentioning
confidence: 99%